Child Delinquency and Pupils’ Academic Performance in Fumesua Municipal Assembly Primary School in the Ejisu- Juaben Municipality, Ashanti Region, Ghana - Esilfie, Gabriel (2015)
This research was conducted purposely to examine child delinquency on pupils’ academic performance. Fumesua Municipal Assembly (M/A) primary school was used as the case study for the research. The specific objectives of the study are to find out the factors that contribute to child delinquent behavior, identify, if delinquent behavior influence the child academic performance and to find out the remedies that will help solve the problem. There was review of related literature in order to put the study into perspective. The study selected a sample size of 49 respondents comprising 40 students and 9 teachers who were interviewed, in order to obtain primary data. Secondary data was also gathered from books, journals and the internet. Purposive sampling was the sampling technique used for selecting the pupils. The collected data were analyzed using Statistical Package for Service Solution (SPSS). From the findings of the study, it was realized that, the causes of child delinquency are as a result of financial problem, bad friends, and poor academic performance and for fun. Also from the findings, it was realized that the remedies to child delinquency are punishment, guidance and counseling, proper monitoring of pupils by parents and reporting of children to their teachers when they misbehave. It was recommended that, parents should monitor their children movement and be mindful of the kind of people they walked with. Also it was recommended that children should not be given enough idle time and again classrooms should not be overcrowded. Key words: Child delinquency, academic performance, first cycl